2001
DOI: 10.1021/bp010109q
|View full text |Cite
|
Sign up to set email alerts
|

Separation of a Breast Cancer Cell Line from Human Blood Using a Quadrupole Magnetic Flow Sorter

Abstract: We have developed a quadrupole magnetic flow sorter (QMS) to facilitate high-throughput binary cell separation. Optimized QMS operation requires the adjustment of three flow parameters based on the immunomagnetic characteristics of the target cell sample. To overcome the inefficiency of semiempirical operation/optimization of QMS flow parameters, a theoretical model of the QMS sorting process was developed. Application of this model requires measurement of the magnetophoretic mobility distribution of the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 19 publications
(24 reference statements)
2
58
0
Order By: Relevance
“…The effects of flow rates on the QMS performance have been theoretically analyzed and experimentally investigated in previous studies (Hoyos et al, 2000(Hoyos et al, , 2002Nakamura et al, 2001;Williams et al, 1999). This manuscript focuses on the utilization of outlet flow rate control to collect the CD34þ cells with different purity and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of flow rates on the QMS performance have been theoretically analyzed and experimentally investigated in previous studies (Hoyos et al, 2000(Hoyos et al, , 2002Nakamura et al, 2001;Williams et al, 1999). This manuscript focuses on the utilization of outlet flow rate control to collect the CD34þ cells with different purity and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the magnetic force depends only on the magnetic field gradient. While (8) and (9) apply to the magnetic capture of cells by immunomagnetic cell selection [85], the goal in DEP-MAP-FFF is not to trap the cells. In this method, a DEP-FFF separation chamber sits on a periodically varying magnetically polarizable layer that itself overlays a flat magnet (Fig.…”
Section: ) Dielectrophoretic-magnetophoretic-fff (Map-dep-fff)mentioning
confidence: 99%
“…It has been previously demonstrated that using both the batch Miltenyi Biotec MACS system or the flow-through, QMS system performance is partially based on the degree to which a cell is immunomagnetically labeled, quantitatively referred to as a cell's magnetophoretic mobility Nakamura et al, 2001;Williams et al, 1999). In addition, the manufacturer of the MACS system states that the MS column can be used for depletion separations if the target cells are ''strongly magnetically labeled'' (Miltenyi Biotec Catalog, Subsection 14.3).…”
Section: Primary Antibody Saturation Curvesmentioning
confidence: 99%